Abundance Index Slender Walking Catfish With Correlation of Water Quality In Natural Habitat - Khairul Khairul (International Journal of Applied Biology, 2020)
Slender walking catfish (Clarias leiacanthus) has decreased in its natural habitat. Many factors affect the decline of the population, including the conversion of land where natural habitat becomes plantation, the presence of excess arrest, and the quality of water that has been contaminated. The condition of the waters determines fish life, considering that various species of fish can only live on certain conditions. A study related to the correlation of water quality with fish abundance index is needed as a knowledge of determining biological and ecological needs of fish as a biological resource in a water.. The results of this study showed the abundance index of wild-type catfish at January (0.15 Ind./m2), February (0.22 Ind./m2),  and March (0.20 Ind./m2). The correlation analysis of water quality showed pH has a correlation (+) with a value of r (0.827).